2017
DOI: 10.1007/s40141-017-0150-0
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Oncology Prognosis and Cancer Rehabilitation

Abstract: Purpose of reviewThis review examines the delivery of rehabilitation care to cancer patients with relation to disease prognosis. This includes the evaluation when patients are referred for rehabilitation services and the effectiveness of rehabilitation interventions across the cancer continuum.Recent findingsAlthough prognosticating life expectancy is difficult, referrals for rehabilitation interventions appear to be affected by physician attitudes towards patients with advanced disease, in part because of mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 83 publications
1
31
0
Order By: Relevance
“…Physiatrists found that cancer patients were challenging to manage for several reasons, such as symptom management, the stage of cancer, and psychological factors. The current challenge for rehabilitation professionals is to manage patients with advanced stage of cancer who need palliative care, although they have poor prognosis [20]. Silver et al conclude that establishing high-quality comprehensive care for oncology cases requires a strong partnership between rehabilitation and palliative care [21].…”
Section: Discussionmentioning
confidence: 99%
“…Physiatrists found that cancer patients were challenging to manage for several reasons, such as symptom management, the stage of cancer, and psychological factors. The current challenge for rehabilitation professionals is to manage patients with advanced stage of cancer who need palliative care, although they have poor prognosis [20]. Silver et al conclude that establishing high-quality comprehensive care for oncology cases requires a strong partnership between rehabilitation and palliative care [21].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the overwhelming evidence that adequate exercise is a necessary component for optimizing patient health, less than 5% of cancer patients exercise during cancer recovery. 17 Therefore, it is our recommendation that prescribed, individualized exercise should serve as part of the national standard of care for all those diagnosed with and treated for cancer.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…This is due in large part to the challenges in prognosticating life expectancy and trying to craft a thoughtful, efficient, and patient‐centered rehabilitation plan without knowing how much time is available to optimize function. Estimating life expectancy in cancer patients is incredibly difficult, often incorrect, and is becoming more challenging as new oncology treatments emerge and the patient population ages . As a result, both oncologists and physiatrists are skeptical about the role of rehabilitation in patients with terminal cancer, and patients may be underreferred for these services .…”
Section: Futility In Cancer Rehabilitation In Patients With Terminal mentioning
confidence: 99%
“…It is important, however, to couch expectations within a framework that sets reasonable expectations and allows for fallback plans should the patient's medical status acutely change. In doing this, one must consider that both patients and surrogate decision makers are often more optimistic about their prognosis than oncologists and that their desired outcome may be unrealistic . Therefore, revisiting the plan with patients and caregivers regularly is necessary to ensure that the interventions being applied continue to have a reasonable likelihood of success.…”
Section: Futility In Cancer Rehabilitation In Patients With Terminal mentioning
confidence: 99%